2017
DOI: 10.1108/jfmm-07-2016-0068
|View full text |Cite
|
Sign up to set email alerts
|

Online consumer behaviour of mass-customised apparel products

Abstract: Purpose The purpose of this paper is to apply Mowen’s (2000) meta-theoretical model of motivation and personality (3M) and its hierarchy of traits to deeper understand consumer behaviour towards online purchase of mass-customised apparel products. Design/methodology/approach For the current study, the meta-theoretical model of motivation and personality (3M) and its hierarchy of traits proposed by Mowen (2000) were adapted to use in the context of online purchase of mass-customised apparel products. Appropri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 76 publications
0
4
0
1
Order By: Relevance
“…As a product category, sports shoes were selected because of their popularity regardless of the age of shoppers and their appropriateness for customization. Moreover in recent mass customization literature sport shoe category is a key research area (Ribeiro et al, 2017;Runfola et al, 2018, Zhou et al, 2019Kalantari et al,2021) After visiting the NIKEiD customization program, participants were asked to create their own sports shoes using the program and imagining that they would have made a purchase. They could select styles, fabrics, colors, and patterns and add text or logo when customizing their shoes.…”
Section: Methodsmentioning
confidence: 99%
“…As a product category, sports shoes were selected because of their popularity regardless of the age of shoppers and their appropriateness for customization. Moreover in recent mass customization literature sport shoe category is a key research area (Ribeiro et al, 2017;Runfola et al, 2018, Zhou et al, 2019Kalantari et al,2021) After visiting the NIKEiD customization program, participants were asked to create their own sports shoes using the program and imagining that they would have made a purchase. They could select styles, fabrics, colors, and patterns and add text or logo when customizing their shoes.…”
Section: Methodsmentioning
confidence: 99%
“…Based on Mowen's (2000) hierarchy of traits concept, a person's characteristics are captured at four levels, namely, elemental, compound, situational, and surface (Helm, 2006; Mowen, 2000; Ribeiro et al, 2017). The result is an integrated account of how personality interacts with situations to influence feelings, thoughts, and behaviours (Mowen & Carlson, 2003).…”
Section: Future Research Directions Based On Ado‐tcm Frameworkmentioning
confidence: 99%
“…Other determinant factors identified were perceived enjoyment and supposed control of online MC. A separate study spearheaded by Ribeiro, Duarte and Miguel (2017) revealed that situational traits include the need for unique items, touch, simplicity, reality, and apparel involvement. These arguments imply that the changes in the fashion industry have impacted consumer behaviors and attitudes, leading to the establishment of diverse perspectives toward MC.…”
Section: Apparel Mass Customizationmentioning
confidence: 99%